Lyons, Sex Among The Rabble - An Intimate History Of Gender & Power In The Age Of Revolution - Reisinger, Andrew (Teaching history (Emporia, Kan.), 2007)
Clare A. Lyons skillfully crafts a book exploring the evolution of power in colonial and early American Philadelphia. The author asserts that sexuality served as a key category in the formation, contestation, and regulation of gender, race, and class hierarchies and that contrary to popular understandings, Philadelphia at this time was not a city of "chaste Quakers." The mid-eighteenth-century city was a complex environment where inhabitants engaged in a variety of nonmarital and extramarital affairs, where women forged spaces in which they could exercise their autonomy, where sex commerce and bastardy proliferated largely unchecked, and where many such acts and behaviors transgressed lines of gender, race, and class.